Fibroblast growth factor 23 mediates the phosphaturic actions of cadmium - Furutani, Junya; Ito, Mikiko; Kuwahara, Shoji; Hanabusa, Etsuyo; Miyamoto, Ken-ichi; Tominaga, Rieko; Aranami, Fumito; Kido, Shinsuke; Tatsumi, Sawako; Segawa, Hiroko (The Journal of Medical Investigation, 2010)
Phosphaturia has been documented following cadmium (Cd) exposure in both humans and experimental animals. The fibroblast growth factor 23 (FGF23)/klotho axis serves as an essential phosphate homeostasis pathway in the bone-kidney axis. In the present study, we investigated the effects of Cd on phosphate (Pi) homeostasis in mice. Following Cd injection into WT mice, plasma FGF23 concentration was significantly increased. Urinary Pi excretion levels were significantly higher in Cd-injected WT mice than in control group. Plasma Pi concentration decreased only slightly compared with control group. No change was observed in plasma parathyroid hormone and 1,25-dihydroxy vitamin D3 in both group of mice. We observed a decrease in phosphate transport activity and also decrease in expression of renal phosphate transporter SLC34A3 [NaPi-IIc/NPT2c], but not SLC34A1 [NaPi-IIa/NPT2a]. Furthermore, we examined the effect of Cd on Npt2c in Npt2a-knockout (KO) mice which expresses Npt2c as a major NaPi co-transporter. Injecting Cd to Npt2aKO mice induced significant increase in plasma FGF23 concentration and urinary Pi excretion levels. Furthermore, we observed a decrease in phosphate transport activity and renal Npt2c expression in Cd-injected Npt2a KO mice. The present study suggests that hypophosphatemia induced by Cd may be closely associated with the FGF23/klotho axis. J. Med. Invest. 57: 95-108, February, 2010